Is clean energy contested? Exploring which issues matter to stakeholders in the European Green Deal. (July 2021) - Ringel, Marc; Bruch, Nils; Knodt, Michèle
Highlights: EU stakeholders show strong support for more ambitious clean energy policies. Future discussion will focus on energy efficiency and renewable energy targets. The concept of salience is validated in the EU energy and climate fields. Results rest on 198, 128 Twitter messages, 182 position papers and 20 survey replies. Abstract: The European Green Deal aims at decarbonizing the European Union's economies by 2050. This implies stepping up policy actions to support both renewable energy and energy efficiency, two domains in which the body of EU law has recently changed. These changes raise the question of stakeholder support for more ambitious policies. To assess such support, we first apply the concept of salience to identify the most important issues for four core European stakeholder groups and follow up with an in-depth investigation. We use a mixed method design, testing external issue salience through a qualitative read-out of 182 stakeholder position papers and 198, 128 Twitter messages, and then testing internal salience and readiness to support through analysis of an opinion survey of 20 key European stakeholders. We find stakeholders closely align in demanding binding energy efficiency and renewable energy policies. Strong focus can be expected on energy efficiency targets and measures, less so on the further development of the framework for renewable energies. These findings confirm earlier studies on salience in different policy fields.